Incidence of reproductive abnormalities in small ruminants - KHATUN, A; WANI, G M; CHOUDHURY, A R; KHAN, M Z; ISLAM, R; PANDIT, B A (The Indian Journal of Animal Reproduction, 2007)
A total of 86 female genitalia of sheep and goat were collected from the abattoirs of Srinagar. Variousabnormalities observed were, parasitic cyst (Taenia hydatigena, 8.14 %), cystic ovary (follicular cyst, 3.49 %;Juteal cyst, 1.16 %), endometritis (1.16 %), mummified fetus (1.16 %), macerated fetus (3.49 %), pyometra (1.16%), ovaro-bursal adhesion (1.16 %), double os cervix (1.16 %), bent cervix (29 % in sheep and 2.33 % in goat).Photographs of the pathological observations are presented.
Keywords: Cyst; Pyometra; Mummified fetus; Macerated fetus